Ultra-Low Ultraviolet Photon Detection of Diamondene Van der Waals Heterostructure by Interfacial Bonding - Jiapeng Zhen; Silin Guo; Ying Yue; Shuai Huang; Danping Zhang; Kai Shen; Kehong Lv; Qiushi Huang; Jing Qiu; Guanjun Liu (Research)
With the increasing demand for high sensitivity, low interference, and micro-size of deep ultraviolet spectral information in the field of photoelectric detection, low-dimensional diamond-based ultraviolet photoelectric detection has attracted great interest. However, although the diamond-based material has a high mobility, its lack of free electrons seriously hinders its conductivity and detection ability. Therefore, improving the free electron level of diamond-based materials has become the primary goal for achieving high-performance applications. Here, we demonstrate a diamondene photodetector formed by van der Waals heterostructure bonding, which has a high level of free electrons and is more advantageous for ultraviolet light. The diamondene photodetector realized by this method has a high responsivity of 2.04 A/W and D* higher than 1012 Jones, and the external quantum efficiency is as high as [Formula: see text]. In the detection of imaging applications, ultraviolet imaging with very low photon number is realized, and clear imaging can be achieved only under the light intensity with a photon number of 28. It is of great substantial for the development and theoretical research of ultra-high sensitivity ultraviolet photodetectors in the future.